Stability and minimum lateral bracing for stepped columns with semi-rigid connections including shear effects: ii) verification and examples (2012)
The elastic stability analysis of single-stepped columns with sidesway totally inhibited, partially inhibited, and uninhibited subjected to concentrated axial loads located at the ends and at the intermediate joint including semi-rigid connections and shear force effects are presented using three different approaches in a companion paper. The first two approaches are those by Engesser and Haringx that include the shear component of the applied axial force proportional to the total slope (dy/dx) and to the angle of rotation of the cross section (Ψ) along the member, respectively. The third approach is a simplified formulation based on the classical Euler theory that includes the effects of shear deformations but neglects the shear component of the applied axial force along the member. Definite criterion on minimum stiffness of lateral bracings for single-stepped columns is also presented. Five comprehensive examples are included that demonstrate the effectiveness of the proposed stability equations and minimum bracing stiffness criteria.